Evaluation of the Implementation of the Kampus Mengajar Program Based on the CIPP Model - Marliza Oktapiani; Sutiono Sutiono; Ifham Choli (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study discussed the evaluation of the implementation of the Kampus Mengajar program, which was carried out after the first batch of Kampus Mengajar programs finished. This research took place at SDIT Al-Karimah, Jakarta, with a six- month program. This program used the CIPP model, which includes Context, Input, Process, and Product. The results of this study showed that in context, there was a frequent reference to the technical instructions for the Kampus Mengajar program, the objectives of the Kampus Mengajar program, and obtaining initial school mapping information. Input was carried out with initial plans and observations as well as strategies and goals to be achieved by students on student literacy and numeracy, an adaptation of technology, and administrative disciplines. In the process, the implementation of education guided the basic literacy education program. Finally, the product showed progress in student learning outcomes and achievement of student reporting in participating in Kampus Mengajar programs with various assessments of teaching outcomes that focused on literacy and numeracy, developments in technology adaptation, administrative management, and assessment of Kampus Mengajar.